Development of Audio Visual Media for Learning Writing Poetry and Poetry for Class X High School Students - Revalinda, Revalinda (Program Magister Teknologi Pendidikan Universitas Jambi, 2024)
This research aims to develop learning media in the form of audio visuals that are effective in improving the ability to write poetry and rhymes in class X high school students. The research method used is the ADDIE model development method (Analysis, Design, Development, Implementation, and Evaluation). The evaluation instruments used include writing ability tests, observations, and questionnaires. The results of this research show that the learning media is suitable for use in learning based on qualitative assessments by the validation team. Apart from that, the product being developed can also make learning easier for students in accordance with student responses that have been carried out in small group trials and field (class) trials. It is hoped that the research results can contribute to the development of innovative and technology-oriented learning methods, and can increase students' interest and ability in writing poetry and rhymes.